Appendix to the foregoing address [by the President, Hon. Judge Longfield, at the opening of the eighteenth session] - (:unkn) unknown (Statistical and Social Inquiry Society of Ireland, 1865)
Some people say that no legislation ought to take place until it is called for by the landlords, who, from experience, ought to know the best way of managing their own properties, quieta non moveri, or in vulgar English, ?to let well enough alone? is often a very good maxim for a statesman. But it is reasonable to ask, ?is this the case of the quieta? or the ?well enough?? I am afraid, however, that it is impossible to deny that some change is required. Many persons may reasonably doubt whether legislation may do much to remove the evils which undoubtedly exist; but they ought to admit that proposals for their relief ought to be calmly and deliberately discussed, and neither be intemperately demanded, nor contemptuously rejected without examination.
Read Saturday, 26th November, 1864
Keywords: Legislative interference between landlords and tenants; Farm valuation; Law of distress; 314.15